Conformational Studies on Aryl-cyclopentadienylidenes: Electronic Effects of Aryl Groups - VESSALLY, E. (Asian Journal of Chemistry, 2010)
The total energy, ET; zero-point energy, thermal energies (E), enthalpies (H) and Gibbs free energies (G) were calculated for aryl substituted divalent five membered cyclic compounds Ar-C4H3G (G = –NH2, –OH, –CH3, –F, –Cl, –Br, –H, –CF3 and –NO2) at B3LYP/6–31+G* and B3LYP/6– 311++G** levels of theory. It could be concluded that an allenic character was constructed instead of carbenic character for both singlet and triplet states of Ar-C4H3G.